If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 13x + 40 = 0 Reorder the terms: 40 + X + 13x = 0 Solving 40 + X + 13x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + X + -40 + 13x = 0 + -40 Reorder the terms: 40 + -40 + X + 13x = 0 + -40 Combine like terms: 40 + -40 = 0 0 + X + 13x = 0 + -40 X + 13x = 0 + -40 Combine like terms: 0 + -40 = -40 X + 13x = -40 Add '-13x' to each side of the equation. X + 13x + -13x = -40 + -13x Combine like terms: 13x + -13x = 0 X + 0 = -40 + -13x X = -40 + -13x Simplifying X = -40 + -13x
| 4x-50-10x=22 | | 6y-25=125 | | 4x-5p-10x=22 | | -10x-154-5x=41 | | 6y^2-7y+7=0 | | f(8)=(2x-8) | | -50=-t^2-5t | | 8x^2-21xy-9y^2=0 | | 3a+5=-28 | | 5w-5=5w+5 | | 36x+2=4 | | 2-16t=(-3t+2) | | 0.13y+0.05(y+6000)=1380 | | 18r=24r^2 | | 15y^2-15y+7=0 | | 2p(6p-18)=0 | | (x-9)(2x+4)=0 | | 25x^2/(5x-2) | | 7x-3=67forx | | 12x+72-30= | | 3h^2+6h=0 | | -3/7x=-6 | | f(5)=(2x-8) | | 16x^4+22x^3-4x^2= | | 4x^2-1x+1=0 | | 3x√35/7 | | 6m^5/2m^2 | | 2(X-15)=X/2 | | f(4)=(2x-8) | | 4x^2-1=63 | | f(1/3)=3x-1 | | 5x×2=210/3 |